Varroa destructor mite in Africanized honeybee colonies Apis mellifera L. under royal jelly or honey production - Pedro da Rosa Santos (Acta Scientiarum. Animal Sciences, 2015)
This study evaluated the level of invasion of Varroa mite into worker brood cells, the infestation rate on adult worker honeybees, total and effective reproduction rates of the mite in Africanized honeybee colonies under royal jelly or honey prod uction. Invasion and infestation rates were not statistically different between honeybee colonies produc ing honey or royal jelly an d the averages for these parameters were 5.79 and 8.54%, respectively. Coloni es producing honey presented a higher (p < 0.05) total and effective reproduction of Varroa than colonies producing royal jelly. There was a negative correlation between levels of invasion and infestation with minimum external temperature, relative humidity and rainfall. The variables month and season influenced the development of the mite, but rates were low and within the range norm ally found in Brazil for Africanized honeybee colonies, which confirm the greater resistance of these honeybees to Varroa destructor than European honeybees.